Production of Inga vera Willd and Eugenia involucrata DC. seedlings fertigated with whey - da Silva, Rita de Cássia; Pinto, Lilian Vilela Andrade (Revista Agrogeoambiental, 2020)
Residuary effluents from dairy industry contaminate hydric resources, so researches aiming sustainable methods to revert this situation must be stimulated. The objective of this study was to determine if whey can be used as fertigation and to define the proportion of whey that shall be fertigated for species Inga vera and Eugenia involucrata. This research consisted in two experiments, one with Inga vera and the other with Eugenia involucrata, since the species have distinct ecological behavior, being pioneer and late secondary, respectively. Both experiments were designed in completely randomized blocks and four fertigations were evaluated: T1: 100% water; T2: 25% whey and 75% water; T3: 50% whey and 50% water; and T4: 100% whey. The indicators evaluated were: plant height, collar diameter, aerial part weight, root weight, and development quality rate. Fresh whey promoted different responses in the development of Eugenia involucrata and Inga vera seedlings and the use of whey as fertigation for the species Eugenia involucrata is not recommended. Studies of irrigation using whey at the concentration of 100% is recommended for the production of Inga vera seedlings, daily or in alternate days, minimizing pressure on clean water availability.